1999
DOI: 10.1085/jgp.114.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates Transepithelial Sodium Transport by Activation of a Protein Phosphatase That Increases Na-K Atpase Activity in Endometrial Epithelial Cells

Abstract: The objective of this study was to investigate the effects of insulin and insulin-like growth factor I on transepithelial Na+ transport across porcine glandular endometrial epithelial cells grown in primary culture. Insulin and insulin-like growth factor I acutely stimulated Na+ transport two- to threefold by increasing Na+-K+ ATPase transport activity and basolateral membrane K+ conductance without increasing the apical membrane amiloride-sensitive Na+ conductance. Long-term exposure to insulin for 4 d result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 47 publications
(79 reference statements)
4
35
0
1
Order By: Relevance
“…The observation that amiloride and benzamil produced inhibition of the basal I sc and that this decrease in current was associated with inhibition of the apical-tobasolateral and net Na + flux strongly suggested that ENaC Na + channels were involved in Na + absorption across this epithelium. This result was consistent with previous studies of Na + transport across the porcine, murine and human endometrial epithelium (Vetter and O'Grady, 1996;Deachapunya et al, 1999;Palmer-Densmore et al, 2002;Chan et al, 2001;Matthews et al, 1998). In native porcine endometrial tissues mounted in Ussing chambers, the surface epithelial cells exhibited a basal I sc that was blocked by amiloride with an IC 50 value (0.8·µmol·l -1 ) identical to that reported for the shell gland epithelium in this study (Vetter and O'Grady, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observation that amiloride and benzamil produced inhibition of the basal I sc and that this decrease in current was associated with inhibition of the apical-tobasolateral and net Na + flux strongly suggested that ENaC Na + channels were involved in Na + absorption across this epithelium. This result was consistent with previous studies of Na + transport across the porcine, murine and human endometrial epithelium (Vetter and O'Grady, 1996;Deachapunya et al, 1999;Palmer-Densmore et al, 2002;Chan et al, 2001;Matthews et al, 1998). In native porcine endometrial tissues mounted in Ussing chambers, the surface epithelial cells exhibited a basal I sc that was blocked by amiloride with an IC 50 value (0.8·µmol·l -1 ) identical to that reported for the shell gland epithelium in this study (Vetter and O'Grady, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…In native porcine endometrial tissues mounted in Ussing chambers, the surface epithelial cells exhibited a basal I sc that was blocked by amiloride with an IC 50 value (0.8·µmol·l -1 ) identical to that reported for the shell gland epithelium in this study (Vetter and O'Grady, 1996). Similar effects of amiloride and benzamil on basal I sc were reported for cultured porcine glandular endometrial epithelial cells maintained under serum-free conditions (Deachapunya et al, 1999). Analysis of tissue morphology (Fig.·1) indicated the presence of lamellae that were clearly distinct from the mucosal morphology of mammalian endometrium (Vetter and O'Grady, 1996).…”
Section: Discussionsupporting
confidence: 84%
“…2A shows that pre-incubation of ATII cells with genistein, a broad tyrosine-kinase inhibitor, completely prevented insulin-induced Na + /K + -ATPase recruitment without affecting the basal levels. Previous studies reported the participation of the PI3K-signaling system in the activation of Na + /K + -ATPase in fibroblast and kidney epithelial cells (Deachapunya et al, 1999;Ragolia et al, 1997;Sweeney et al, 2001). Incubation with 100 nM wortmannin or LY 294002, two PI3K inhibitors, markedly prevented insulin-induced Na + /K + -ATPase translocation (Fig.…”
Section: Atpase Activitymentioning
confidence: 69%
“…The insulin receptor tyrosine kinase is the first protein activated in the insulin-signaling network (Deachapunya et al, 1999). Fig.…”
Section: Atpase Activitymentioning
confidence: 99%
“…In the primary culture of mouse and porcine endometrial epithelial cells, prostaglandins (PGs) especially PGE2, adrenaline, ATP, and UTP were found to activate anion secretion (Chan et al 1997, Fong et al 1998, Deachapunya & O'Grady 1998, Palmer-Densmore et al 2002. These epithelial cells also exhibited Na C transport that was activated by insulin and insulin-like growth factor, and inhibited by epidermal growth factor (Deachapunya et al 1999, Deachapunya & O'Grady 2001.…”
Section: Introductionmentioning
confidence: 99%